Financial accounting : IFRS - Weygandt, Jerry J.; Kieso, Donald E.; Kimmel, Paul D. (John Wiley & Sons, 2011)
* Explains the business reason for making accounting decisions * Introduces challenging accounting concepts with examples that are familiar * US public companies will have to follow International Financial Reporting Standards as of January 1, 2011, Weygandt's Financial Accounting: IFRS introduces these